Stability of gentamicin, tobramycin, and amikacin in combination with four beta-lactam antibiotics. - Glew, R H (1983)
The stability of the aminoglycosides gentamicin, tobramycin, and amikacin stored in combination with carbenicillin, piperacillin, cefotaxime, and moxalactam was evaluated at four temperatures (25, 4, -8, and -70 degrees C) over a 3-week period. Amikacin was the most stable of the aminoglycosides and demonstrated no loss of activity when stored with either carbenicillin or piperacillin. Gentamicin and tobramycin were inactivated by carbenicillin and piperacillin at 25 and 4 degrees C, with aminoglycoside activity declining substantially after 8 to 48 h of storage; virtually no loss of gentamicin or tobramycin activity occurred with storage at -8 or -70 degrees C. Cefotaxime and moxalactam produced no degradation of any of the three aminoglycosides.